Ayurvedic Management Of Darunak W.S.R. To Dandruff – A Review - Goud, Prem Kumar; Pamnani, Gulab Chand (International Research Journal of Ayurveda & Yoga, 2020)
According to Ayurveda Tvak and Nakha are the Updhatu of Asthi dhatu which is formed from asthi dhatu metabolism. In some individuals tvak is very sensitive organ; even environmental changes like cold, heat and other factors like cosmetics and chemical shampoo also occurred harmful effect on it that sometimes leads to kapalgat roga like darunaka w.s.r. Dandruff. Darunaka is also considering under the umbrella of kshudra rogas in Ayurveda. It is caused due to unbalance of dosha. Main Dosha are involved in darunaka is Kapha and Vata dosha. The condition like darunaka can be managed by comprehensive approach like diet, detoxification procedures along with some internal medication.